Q: What is x in -6x 4 2?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(-6x)(-12x)(-4) = -(6x)(12x)(4) = -[(6)(12)(4)][(x)(x)] = -(288)(x^2) = -288x^2

10

6x + 2 = 6 6x = 4 x = 2/3

is it 6+6x-2. If it is than it should be 6x+4. Then you can solve for X. Which gives you X=-2/3

(x + 3)^2 - 13 = (x + 2)^2 x^2 + 6x + 9 -13 = x^2 + 4x + 4 x^2 + 6x - 4 = x^2 + 4x + 4 6x - 4x = 4 + 4 2x = 8 x = 4

Related questions

(-6x)(-12x)(-4) = -(6x)(12x)(4) = -[(6)(12)(4)][(x)(x)] = -(288)(x^2) = -288x^2

10

6x + 2 = 6 6x = 4 x = 2/3

is it 6+6x-2. If it is than it should be 6x+4. Then you can solve for X. Which gives you X=-2/3

root (6x - 2) = 4 therefore 6x - 2 = 16 therefore 6x = 16 + 2 therefore x = 3

(-6x+4)(x+5) -6x^2 +4x -30x +20 -6x^2 -26x + 20

8x+2=6x+10 8x-6x=10-2 2x=8 x=4 Therefore, x=4.

(x + 3)^2 - 13 = (x + 2)^2 x^2 + 6x + 9 -13 = x^2 + 4x + 4 x^2 + 6x - 4 = x^2 + 4x + 4 6x - 4x = 4 + 4 2x = 8 x = 4

x-intercept is at y=0y=x^2+6x+80=x^2+6x+80=(x+4)(x+2)x=-4,-2x-intercepts are at (4,0) and (-2,0)

6x+4 = x+12+4x-6 6x-x-4x = 12-6-4 x = 2

4x-6 = -6x-4 4x+6x = 6-4 10x = 2 x = 2/10 x = 1/5 Regards, A Pakistani!

(6x^5 + 12x) / (-2x^-3) =[ (6x^5 + 12x) (x^3) ] / (-2) =(6x^8 + 12x^4) / (-2)=(3x^8 + 6x^4) =(3x^4)[ (x^4) + 2 ]